Utilization of carbon dioxide by growing industrial microalgae in power based fuel cells - Palchik, A.; Burega, N.; Fendo, O. (Energy and Automation, 2015)
A block diagram of the energy system based fotoanaereobnyh biotechnology and solid oxide fuel cell.